Antioxidant activity of cerium dioxide nanoparticles and nanorods in scavenging hydroxyl radicals. Issue 20 (9th April 2019) - Filippi, Alexander; Liu, Fobang; Wilson, Jake; Lelieveld, Steven; Korschelt, Karsten; Wang, Ting; Wang, Yueshe; Reich, Tobias; Pöschl, Ulrich; Tremel, Wolfgang; Tong, Haijie
Abstract : Cerium dioxide nanoparticles and nanorods were found to exhibit much stronger scavenging activity than ·OH generation in quasi-physiological conditions. Abstract : Cerium oxide nanoparticles (CeNPs) have been shown to exhibit antioxidant capabilities, but their efficiency in scavenging reactive oxygen species (ROS) and the underlying mechanisms are not yet well understood. In this study, cerium dioxide nanoparticles (CeNPs) and nanorods (CeNRs) were found to exhibit much stronger scavenging activity than ·OH generation in phosphate buffered saline (PBS) and surrogate lung fluid (SLF). The larger surface area and higher defect density of CeNRs may lead to higher ·OH scavenging activity than for CeNPs. These insights are important to understand the redox activity of cerium nanomaterials and provide clues to the role of CeNPs in biological and environmental processes.